Leading edge erosion of wind turbine blades: Effects of blade surface curvature on rain droplet impingement kinematics. Issue 5 (September 2020) - Verma, Amrit S.; Castro, Saullo G.P.; Jiang, Zhiyu; Hu, Weifei; Teuwen, Julie J.E.
Abstract: The issue of leading edge erosion (LEE) of wind turbine blades (WTBs) is a complex problem that reduces the aerodynamic efficiency of blades, and affects the overall cost of energy. Several research efforts are being made at the moment to counter erosion of WTBs such as-testing of advanced coating materials together with development of high-fidelity computational models. However, the majority of these studies assume the coated surfaces as flat, while the surface curvature and the shape of the aerofoil at the blade's leading-edge exposed to such rain fields is neglected. The present study questions the assumption of a flat surface, in the context of LEE of WTBs, and provides guidelines for erosion modelling. The critical parameters associated with rain droplet impingement kinematics on leading edge are compared for blade impact with (a) flat surface assumptions together with (b) the effects of the blade's surface curvature. A parametric study is performed which includes WTBs of varying sizes and power ratings ranging from 750 KW to 10 MW, different positions along the blade length, and different rain droplet radii ranging from 0.1 mm to 5 mm for a land based wind turbine operating at rated wind speed. It is found in the study that droplet impingement kinematics are influenced by the surface curvature at the leading edge, the effect of which is significant for representing erosion at the blade tip for smaller blades, and for exposure to rainfall intensity with larger rain droplet size. A master curve describing the threshold level along the blade length is established for various WTBs and rainfall conditions, where flat surface approximation of the surface yields noticeable error and violates the impingement process. The results of the study are expected to aid the modeller in developing advanced numerical models for LEE for WTBs.